APLIKASI PENJADWALAN MATA KULIAH JURUSAN TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA DENGAN ALGORITMA GENETIKA - Saputra, Ade Chandra; Saragih, Agus Sehatman (Universitas Palangka Raya, 2018)
Scheduling courses in informatics engineering is needed to arrange an optimalschedule so that there is no conflict when teaching courses. In this journal of informaticsengineering has a problem in making a schedule because of frequent clash of teachinghours and the room used.Based on the problem, then to solve the above problem is to use the geneticalgorithm method. The genetic algorithm method is used for scheduling optimization.The final result of this research is the website program of Scheduling Courses inthe Department of Informatics, Faculty of Engineering, Palangkaraya University, whichcan display information about course schedules and this will be a tool for departments toprocess scheduling data through the course scheduling application.